How and when to use common biomarkers in community-acquired pneumonia. Issue 1 (December 2016) - Shaddock, Erica
Abstract Community-acquired pneumonia (CAP) is a leading cause of death in both the developed and developing world. The very young and elderly are especially vulnerable. Even with appropriate early antibiotics we still have not improved the outcomes in these patients since the 1950s, with 30-day case fatality rates of between 10–12 %. Interventions to improve outcomes include immunomodulatory agents such as macrolides and corticosteroids. Treating doctors identify CAP patients who are likely to have poor outcomes by using severity scores such as the pneumonia severity index and CURB-65, which allows these patients to be placed in ICU settings from the start of the admission. Another novel way to identify these patients is with the use of biomarkers. This review illustrates how various biomarkers have been shown to predict mortality, complications and response to treatment in CAP patients. The evidence using either procalcitonin or C-reactive protein to demonstrate response to treatment and hence that the antibiotics chosen are appropriate can play an important role in antibiotic stewardship.